UPAYA BADAN USAHA MILIK NEGARA (BUMN) MENJADI AKTOR REGIONAL DI VIETNAM MELALUI PT SEMEN INDONESIA TAHUN 2012 - Wanti Wahyuning Tiyas; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is the study of international relations, especially the international political economy that will discuss the efforts of the State Owned Enterprises (SOEs) into a regional actor in Vietnam through PT Semen Indonesia in 2012. The move to realize the policy of SOE Minister Dahlan Iskan will encourage SOEs moves to scale world class company.The authors need to retrieve data from the journal, official documents, books, and intenet to analyze the efforts of state-owned enterprises into a regional actor in Vietnam through PT Seman Indonesia in 2012. The theoretical framework that I use in research is Neoliberal Perspective, Level of Analysis Group and trade theory international of the Heckscher-Ohlin (HO) and the Role Theory of Petter Evans.Implementation of PT Semen Indonesia embodied as a company with the scale of a world class company is doing good corporate governance and establish Semen Indonesia Center of The Champs to improve the performance of employees who are ready to compete. Expansion of the region with a 70% stake TLCC as well as engaging with the local community Vietnam on Corporate Social Responsibility program.Keywords: State Owned Enterprises, Thang Long Cement Joint Stock Company, World Class Company